2022
DOI: 10.3390/polym14224978
|View full text |Cite
|
Sign up to set email alerts
|

Triborheological Analysis of Reconstituted Gastrointestinal Mucus/Chitosan:TPP Nanoparticles System to Study Mucoadhesion Phenomenon under Different pH Conditions

Abstract: Polymeric nanoparticles have attracted much attention as pharmaceutical delivery vehicles to prolong residence time and enhance the bioavailability of therapeutic molecules through the mucoadhesive phenomenon. In this study, chitosan:TPP nanoparticles were synthetized using the ionic gelation technique to analyze their mucoadhesive interaction with reconstituted porcine gastrointestinal mucus from a triborheological point of view under different pH conditions (pH = 2.0, 4.0, 6.0 and 7.0). The triborheological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Notably, this technology is safe owing to the mucoadhesion of crosslinked LMWC via secondary interactions, which are not expected to cause irritation, inflammation, or ulceration of the gastric mucosa [ 10 , 11 ]. Additionally, with an adhesion force of 89 mN under normal stomach conditions and shear stresses (peristaltic movement), the capsules can be readily detached [ 49 ]. Other studies have demonstrated that chitosan crosslinked with TPP can adhere to stomach conditions for up to 90 h and is easily cleared from the digestive tract [ 10 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, this technology is safe owing to the mucoadhesion of crosslinked LMWC via secondary interactions, which are not expected to cause irritation, inflammation, or ulceration of the gastric mucosa [ 10 , 11 ]. Additionally, with an adhesion force of 89 mN under normal stomach conditions and shear stresses (peristaltic movement), the capsules can be readily detached [ 49 ]. Other studies have demonstrated that chitosan crosslinked with TPP can adhere to stomach conditions for up to 90 h and is easily cleared from the digestive tract [ 10 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, with an adhesion force of 89 mN under normal stomach conditions and shear stresses (peristaltic movement), the capsules can be readily detached [ 49 ]. Other studies have demonstrated that chitosan crosslinked with TPP can adhere to stomach conditions for up to 90 h and is easily cleared from the digestive tract [ 10 , 49 , 50 ]. Moreover, all components of the system are food-grade and FDA-approved for use in food formulations [ 17 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A prepared blend solution (1 ml) for each formulation was placed on the Peltier plate surface and held for 2–3 min at room temperature for stress relaxation and temperature equilibration. The results obtained were analyzed using TRIOS software (TA Instruments, Delaware, USA), and values for viscosity (η, Pa.s) and shear rate (γ, s‐ 1 ) were used to plot the results and the correlation with the reinforced material into the blends [35,62,63] …”
Section: Methodsmentioning
confidence: 99%
“…The results obtained were analyzed using TRIOS software (TA Instruments, Delaware, USA), and values for viscosity (η, Pa.s) and shear rate (γ, s-1 ) were used to plot the results and the correlation with the reinforced material into the blends. [35,62,63]…”
Section: Rheological Testmentioning
confidence: 99%
“…The morphological characteristics of selected nanoparticles both as powder and suspension were observed following the method modified from Ruiz-Pulido et al [31] using a scanning electron microscopy (SEM, Quanta 450, FEI Co., OR, USA). Before analysis, sample suspensions were prepared by dispersing the freeze-dried nanoparticles in absolute ethanol at a concentration of 0.05 mg mL −1 .…”
Section: Methodsmentioning
confidence: 99%